Gender Issues on the Geography of Emotions About Covid-19 in Adolescents - Darmawan, Dadang; Andriyani, Septian; Roha, Aida; Darmawati, Irma; Tuty Putri, Suci (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: The COVID-19 pandemic emerged abruptly and is characterized by its high transmissibility, resulting in heightened levels of anxiety and depression within the community. Indonesia represents one of the nations significantly impacted by the COVID-19 pandemic. Since the onset of the virus, children and adolescents have experienced increased feelings of anxiety and stress. Emotional disorders can be precipitated in children and adolescents exhibiting symptoms of anxiety, fear, stress, restlessness, or worry. Objective: The objective of this study was to explore gender-related issues in the emotional landscape of COVID-19 among junior high school students. Method: The research employs a quantitative approach. Data collection was executed through a Google Form containing a series of statements. The instrument utilized for data gathering was the 2020 COVID Stress Scales (CSS), which comprises 36 statement items. The population under investigation consisted of 1,640 students, from which a sample of 328 junior high school students was selected based on predefined inclusion and exclusion criteria. Results: The findings indicated that the emotional geography of students exhibited the highest mean score in the Xenophobia domain, with an average value of 3.394, while the lowest mean score was observed in the Compulsive Checking Emotional Geography, with an average value of 2.107; moreover, a statistically significant difference in mean values was noted. Emotional geography, particularly within the socio-economic domain, displayed differences between boys and girls, with a p-value of 0.000. Conclusion: Distinct emotional differences between boys and girls were identified in relation to contamination, xenophobia, and socio-economic ramifications. It is imperative for schools and parents to provide psychological support, facilitate the dissemination of information, and offer behavioral guidance at both individual and community levels.